Antimicrobials in agriculture: reducing their use while limiting health and socioeconomic risks in the countries of the South - Roger, François; Ducrot, Christian (Perspective, 2017)
<span style="font-size: 10pt; font-family: Arial; font-style: normal;" data-sheets-value=""1":2,"2":"The widespread use of antimicrobials in agriculture is increasing, driven by growth in intensive livestock production and demand for animal products. This is creating a serious problem of antimicrobial resistance: bacteria are developing antimicrobial resistance mechanisms, which spread through populations of bacteria, including those affecting humans. Antimicrobial resistance has a major impact on public health, and its effects on animal health and biodiversity are not yet fully understood. To address this alarming situation, reducing and rationalising the use of antimicrobials is a global priority, in the North and the South alike. This calls for intersectoral actions involving professionals and researchers from many different scientific fields: domestic animals, wildlife, plants, humans and the environment. Implementing such actions is particularly complex in the countries of the South."" data-sheets-userformat=""2":585,"3":[null,0],"6":"1":["1":2,"2":0,"5":[null,2,0],"1":0,"2":0,"3":3,"1":1,"2":0,"4":1],"9":0,"12":0">Version française de l'article <span style="font-size: 10pt; font-family: Arial; font-style: normal;" data-sheets-value=""1":2,"2":"The widespread use of antimicrobials in agriculture is increasing, driven by growth in intensive livestock production and demand for animal products. This is creating a serious problem of antimicrobial resistance: bacteria are developing antimicrobial resistance mechanisms, which spread through populations of bacteria, including those affecting humans. Antimicrobial resistance has a major impact on public health, and its effects on animal health and biodiversity are not yet fully understood. To address this alarming situation, reducing and rationalising the use of antimicrobials is a global priority, in the North and the South alike. This calls for intersectoral actions involving professionals and researchers from many different scientific fields: domestic animals, wildlife, plants, humans and the environment. Implementing such actions is particularly complex in the countries of the South."" data-sheets-userformat=""2":585,"3":[null,0],"6":"1":["1":2,"2":0,"5":[null,2,0],"1":0,"2":0,"3":3,"1":1,"2":0,"4":1],"9":0,"12":0">The widespread use of antimicrobials in agriculture is increasing, driven by growth in intensive livestock production and demand for animal products. This is creating a serious problem of antimicrobial resistance: bacteria are developing antimicrobial resistance mechanisms, which spread through populations of bacteria, including those affecting humans. Antimicrobial resistance has a major impact on public health, and its effects on animal health and biodiversity are not yet fully understood. To address this alarming situation, reducing and rationalising the use of antimicrobials is a global priority, in the North and the South alike. This calls for intersectoral actions involving professionals and researchers from many different scientific fields: domestic animals, wildlife, plants, humans and the environment. Implementing such actions is particularly complex in the countries of the South.